Development of a cancer pain self-management resource to address patient, provider, and health system barriers to care. Issue 4 (August 2019) - Luckett, Tim; Davidson, Patricia M.; Green, Anna; Marie, Natalie; Birch, Mary-Rose; Stubbs, John; Phillips, Jane; Agar, Meera; Boyle, Frances; Lovell, Melanie
Abstract: Objective: The majority of self-management interventions are designed with a narrow focus on patient skills and fail to consider their potential as "catalysts" for improving care delivery. A project was undertaken to develop a patient self-management resource to support evidence-based, person-centered care for cancer pain and overcome barriers at the levels of the patient, provider, and health system. Method: The project used a mixed-method design with concurrent triangulation, including the following: a national online survey of current practice; two systematic reviews of cancer pain needs and education; a desktop review of online patient pain diaries and other related resources; consultation with stakeholders; and interviews with patients regarding acceptability and usefulness of a draft resource. Result: Findings suggested that an optimal self-management resource should encourage pain reporting, build patients' sense of control, and support communication with providers and coordination between services. Each of these characteristics was identified as important in overcoming established barriers to cancer pain care. A pain self-management resource was developed to include: (1) a template for setting specific, measureable, achievable, relevant and time-bound goals of care, as well as identifying potential obstacles and ways to overcome these; and (2) a pain management plan detailing exacerbating and alleviating factors, current strategies for management, and contacts for support. Significance of results: Self-management resources have the potential for addressing barriers not only at the patient level, but also at provider and health system levels. A cluster randomized controlled trial is under way to test effectiveness of the resource designed in this project in combination with pain screening, audit and feedback, and provider education. More research of this kind is needed to understand how interventions at different levels can be optimally combined to overcome barriers and improve care.